Maya pilgrimage to ritual landscapes : insights from archaeology, history, and ethnography - Palka, Joel W., 1962- (Archaeologies of landscape in the Americas series., 2014)
"Pilgrimage to ritually significant places is a part of daily life in the Maya world. These journeys involve important social and practical concerns, such as the maintenance of food sources and world order. Frequent pilgrimages to ceremonial hills to pay offerings to spiritual forces for good harvests, for instance, are just as necessary for farming as planting fields. Why has Maya pilgrimage to ritual landscapes prevailed from the distant past and why are journeys to ritual landscapes important in Maya religion? How can archaeologists recognize Maya pilgrimage, and how does it compare to similar behavior at ritual landscapes around the world? The author addresses these questions and others through cross-cultural comparisons, archaeological data, and ethnographic insights"--